the optimal length of follow up after successful pediatric pyeloplasty - srithong, supang; Usawachintachit, Manint; Bunyaratavej, Chanatee (Insight Urology, 2019)
Purpose: Ureteropelvic junction obstruction (UPJO) is a common congenital anomaly, and dismembered pyeloplasty is a standard treatment. However, following surgery, the appropriate duration of follow up has not been well described. We conducted this study to investigate the optimal length of follow-up after a successful operation. Method: This is a retrospective study performed in all pediatric patients undergoing pyeloplasty at King Chulalongkorn Memorial Hospital from January 2007 to December 2016. The inclusion criterias were patients who demonstrated improvement in a degree of hydronephrosis from postoperative ultrasound, became asymptomatic and required no further operation. We excluded patients who had bilateral disease, solitary kidney or other associated KUB anomalies. All patients underwent periodic KUB ultrasound to identify the degree of hydronephrosis classified by the Society of Fetal Ultrasound (SFU) system. We assessed the optimal duration of follow up until the degree of hydronephrosis was stable. Results: A total of 42 UPJO patients was included in the study (36 males and 6 females). The median age at surgery was one year, and disease on the left side was slightly predominated (57.1%). Preoperative imaging revealed SFU Grade III hydronephrosis in 4 patients (9.5%) and grade IV in 38 patients (90.5%). The median duration of follow-up was 36 months. Following pyeloplasty, the degree of hydronephrosis stabilized in 73% at 24 months, 80.4% at 36 months, 85.3% at 48 months, 90.2% at 60 months, 97.6% at 72 months, and 100% at 84 months. Conclusion: After successful pyeloplasty, a reduction in the degree of hydronephrosis correlates well with the follow-up duration and stabilizes at seven years. Results from this study may be useful for establishing a guideline for follow-up in the future. Keywords: Ureteropelvic junction obstruction (UPJO), Follow up, Pyeloplasty